Lycopene and Phycocyanin - biological properties in experimental diabetes: 1. Effects on blood parameters and liver carbohydrates - MOLDOVAN, Alin Iulian; ȚIGU, Adrian Bogdan; JULA, Traian Claudiu; MOLDOVAN, Cristian Silviu; POJAR, Sabina; DRULA, Rareș; NISTOR, Mădălina Lorena; MOLDOVAN, Bianca Patricia; GULEI, Diana; ROȘIORU, Corina Luminița (Studia Universitatis Babeș-Bolyai Biologia, 2016)
Type 2 diabetes is one of the fastest rising metabolic diseases of our time, mainly due to an unhealthy lifestyle, diet and lack of exercise. While medical treatment does indeed exist and the quality of life is improved under medication, one must take into account that the predominant geographical areas in which diabetes is on the rise are underdeveloped and as such, access to modern medicine may be hindered. The purpose of our study was to confirm the hypoglycemic and antioxidant effects of two biomolecules in the pathology of diabetes. For this study we used 40 albino male Wistar rats, divided into four groups. The control group (C) received a normal diet and tap water. The untreated diabetic group (D) was intravenously injected with a dose of 50mg/kg streptozotocin after a 12 hour fasting period and given a normal diet and water. Diabetes was induced in the same way for the two treated groups, with their diets being supplemented with 10 mg/kg lycopene (DL group) and an equivalent of 200 mg/kg phycocyanin in the form of Arthrospira powder (DS group). Blood was drawn every 7 days do determine glycemic status and after 14 days the animals were killed under anesthesia, with blood and liver being collected for morphological and biochemical analysis. Blood glucose significantly dropped in the DL group on the 7th day of treatment, with both treatments reducing fasting blood sugar to normal levels on the 14th day. Hepatic glucose was normalized in both DL and DS groups without any significant change in glycogen concentrations. RBC counts revealed a tendency of the erythrocytes to increase in numbers in the treated groups and lycopene appears to restore WBC numbers to normal levels. Taking into account these results, it can be said that both biomolecules have a potent hypoglycemic effect in diabetic hyperglycemia, while also improving carbohydrate metabolism in the liver. Lycopene seems to be the more effective antioxidant of the two, preventing oxidative-induced hemolysis of the red blood cells and restoring normal PCV and hemoglobin levels.